Microfinance and Small Enterprise Development of Urban Market Women in Ghana - Eddy Floide Ignanga Bigoundou; Anita Bans-Akutey; Cynthia Oduro-Nyarko; Emelia Ohene Afriyie; Lawrencia Irene Opare Darko (Goodwood Publishing, 2026)
Purpose: This study examines how microfinance influences small enterprise development among market women in Ghana’s urban market setting. Specifically, this study examined the accessibility of microfinance services to urban market women, assessed the effect of microfinance services on the growth of small enterprises of urban market women, and examined the relationship between microfinance repayment structures and the financial performance of urban market women. Research Methodology: Quantitative data were collected from 278 market women, who were purposively selected from a market in an urban area located in the Greater Accra Region of Ghana, using a structured questionnaire. Results: The findings reveal that microfinance services are relatively accessible to urban market women in Ghana, with a significant positive effect of microfinance services on the growth of small enterprises of urban market women, as well as a significant positive relationship between microfinance repayment structures and the financial performance of small enterprises of urban market women. Conclusions: This study concludes that microfinance serves as a powerful instrument for women’s economic empowerment when implemented using gender-sensitive approaches. Limitations: This study is limited by its focus on urban market women, which overlooks the experiences of rural women and other small-scale entrepreneurs facing different constraints. Contributions: This study shows how microfinance empowers urban market women through improved access to credit, business growth, and enhanced livelihoods. It also advances the understanding of gendered entrepreneurship in Ghana by showing how financial inclusion intersects with women’s economic development.